2001
DOI: 10.1007/bf02463975
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic confirmation of Calonectria spathulata and Cylindrocladium leucothoes based on morphology, and sequence data of the β-tubulin and ITS rRNA genes

Abstract: A Calonectria sp. forming a Cylindrocladium anamorph was found to be commonly associated with leaf spot and cutting rot of Eucalyptus in Brazil, Colombia, Ecuador and Argentina. Based on morphology, isolates of this species resembled Cal. hederae, Ca/. reteaudiiand Cy. leucothoes, taxa that are commonly referred to as the Cal. reteaudii-complex. Using DNA sequence data of the ITS1, 5.8S and ITS2 of the rRNA gene, as well as the/9-tubulin gene, this species was shown to represent a previously described, but rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…(2016), present study Ca. angustata CBS 109065 T AF207543GQ267361FJ918551DQ190696KY653359GQ280548GQ280671Crous and Kang, 2001, Crous et al., 2006a, Lombard et al., 2010c, Lombard et al., 2010d, present study Ca. arbusta CBS 136079 T KJ462904KJ463018KJ462787KJ463135Lombard et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2016), present study Ca. angustata CBS 109065 T AF207543GQ267361FJ918551DQ190696KY653359GQ280548GQ280671Crous and Kang, 2001, Crous et al., 2006a, Lombard et al., 2010c, Lombard et al., 2010d, present study Ca. arbusta CBS 136079 T KJ462904KJ463018KJ462787KJ463135Lombard et al.…”
Section: Resultsmentioning
confidence: 99%
“…madagascariensis CBS 114572 T DQ190572GQ267394GQ267314DQ190658KY653409GQ280592GQ280714Crous et al., 2006a, Lombard et al., 2010c, present study Ca. macroconidialis CBS 114880 T AF232855GQ267393GQ267313DQ190655KY653410GQ280591GQ280713Crous et al., 1999, Crous and Kang, 2001, Lombard et al., 2010c, present study Ca. magnispora CBS 136249 T KJ462956KJ463071KJ462841KJ463187Lombard et al.…”
Section: Resultsmentioning
confidence: 99%
“…Template DNA (20 ng) was amplified in a 25-µL polymerase chain reaction (PCR) reaction mixture consisting of 10 mM KCl; 10 mM (NH 4 ) 2 SO 4 ; 20 mM Tris-HCl (pH 8.8); 6 mM MgSO 4 ; 500 µM each of dATP, dCTP, dGTP, and dTTP, with 60 pmol T1 (O'Donnell and Cigelnik 1997) and bt2b (Glass and Donaldson 1995) primers; and 1.5 units Biotaq (Bioline, London, U.K.) DNA polymerase. The reaction and PCR conditions and protocol were as described in Crous and Kang (2001).…”
Section: Dna Amplification and Sequence Determinationmentioning
confidence: 99%
“…Schub. A recent molecular study comparing isolates of these species, however, found this concept to be too wide (Crous and Kang 2001) and again separated species such as Cy. hederae, Cy.…”
Section: Introductionmentioning
confidence: 99%
“…are associated with forestry-related plants (see Lombard et al. 2010c), where Calonectria leaf blight (CLB) is an important constraint to plantation productivity in South America (Rodas et al., 2005, Alfenas et al., 2015) and Southeast Asia (Crous and Kang, 2001, Old et al., 2003, Chen et al., 2011, Lombard et al., 2015a). In other regions, such as southern Africa and Australia, Calonectria spp.…”
Section: Introductionmentioning
confidence: 99%